Bahasa dan Makna Menurut Bertrand Russell (Sebuah Analisis Filsafat Analitik) - Baso Abiyyu; Wahyudi; Ramsiah Tasruddin (Yayasan Al-Afif, 2025)
Language plays a fundamental role in human life because it is the primary means of thinking, communicating, and understanding reality. In philosophical studies, language is not only seen as a means of communication, but also as a medium that shapes how humans understand the world and truth. Therefore, the issue of language and meaning has become a central theme in modern philosophy, especially in efforts to explain the relationship between language, thought, and reality. This research method uses a qualitative approach with a library research type. The study aims to analyze Bertrand Russell's thoughts on language and meaning within the framework of analytical philosophy. Data sources consist of primary data, namely Bertrand Russell's works relevant to the philosophy of language, and secondary data in the form of books and scientific journal articles discussing analytical philosophy. Analytical Philosophy is a modern philosophical tradition that emphasizes language analysis as the primary tool for explaining and resolving philosophical problems. This tradition developed in the 20th century, especially in England and the United States, and figures such as Bertrand Russell and Ludwig Wittgenstein used language as a primary focus to understand how we think, convey concepts, and solve philosophical problems through logical structures and the use of language in real-life contexts. Bertrand Russell's thinking shows that language has a central role in analytical philosophy as a means to represent reality rationally and systematically. According to Russell, the meaning of a statement is determined by its correspondence with facts, so that the clarity of meaning is very dependent on the logical structure of language. Many philosophical problems arise from the ambiguity of everyday language, so the main task of philosophy is to carry out logical analysis to reconstruct ordinary language expressions into simpler and more precise forms.